Improving access to mental healthcare for displaced Syrians: case studies from Syria, Iraq and Turkey. (2nd January 2018) - Hughes, P.; Hijazi, Z.; Saeed, K.
Abstract : The conflict in Syria has led to an unprecedented humanitarian crisis that extends across multiple countries in the area. Mental health services were undeveloped before and now face huge strain and unmet need. The World Health Organization and others have developed a programme to build capacity in the delivery of mental health services in an integrated healthcare package to refugees and displaced people. The tool used for this is the mhGAP Intervention Guide and complementary materials. In this paper we refer to training in Turkey, Iraq and Syria where health professionals were trained to roll out this community-based integrated approach through primary healthcare. We describe field case examples that show the complexity of situations that face refugees, displaced people and those caught in active conflict. Training improved the knowledge and skills for managing mental health disorders in primary healthcare. Further work needs to be done to demonstrate greater access to and utilisation of services, client outcomes and organisational change with this approach.